Uniplex and Duplex RT-PCR protocol for detection of PLRV and PVY in aphids from potato fields - Venkateswarlu, Vallepu; Sridhar, Jandrajupalli; Raigond, Baswaraj; Arjunan, Jeevalatha; Malik, Kamalesh; Bhatnagar, Anuj; Kumari, Neelum; Sharma, Sanjeev; Mandadi, Nagesh; Singh, Bir Pal; Chakrabarti, S K (Potato Journal, 2017)
Aphids are the principal vectors of economically important potato viruses, especially Potato leafroll virus (PLRV) and Potato virus Y (PVY). Detection of PLRV and PVY from potato plants as well as aphid vectors plays a crucial role for their management. Therefore, coat protein gene targeted uniplex and duplex reverse transcription polymerase chain reaction (RT-PCR) assays were developed to detect PLRV and PVY in aphid collection from major potato growing areas of India (Shillong, Modipuram, Shimla, Jalandhar, Patna, Kodaikanal, Sikkim, Nagaland and Arunachal Pradesh). In addition, aphid species were also identified using mitochondrial COI (mt COI) gene. Complimentary DNA synthesized from the total RNA isolated from aphid collection was used as template DNA for amplification of targeted coat proteins of viruses. Annealing temperature of 62oC was standardized as optimum for amplification of target viruses in both uniplex and duplex assays. The PCR amplified an expected band of 380 bp and 492 bp corresponding to PVY and PLRV, respectively. Further, sequencing of the amplicons also confirmed the coat protein genes of respective viruses. The results also revealed aphid populations from Shillong and Modipuram carried PVY or PLRV. Therefore, this protocol can be successfully employed to detect PLRV and PVY from aphids